Perencanaan Peningkatan Kualitas Infrastruktur pada Kawasan Kumuh (Studi Kasus: Kawasan Permukiman Kumuh Desa Dutohe, Kecamatan Kabila, Kabupaten Bone Bolango) - Seftiyani Toyili; Mohamad Yusuf Tuloli; Arfan Utiarahman (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Based on the Decree (SK) on the Change of Slum Locations in Bone Bolango Regency, Dutohe Village in Kabila District was designated as one of the areas experiencing a decline in residential quality and classified as a light slum area. The existing condition shows that the average damage level of neighborhood roads reaches 40.03%, and the drainage system is not yet optimal with an average value of 33.19%. This study aims to plan infrastructure improvements in the slum settlement area of Dutohe Village and to estimate the cost of planning road and drainage infrastructure as an effort to create a more livable and sustainable settlement area. The research method used is a mixed method, combining quantitative and qualitative approaches through field surveys, interviews, and technical design analysis (Detail Engineering Design). The research results indicate that the proposed technical plan includes the construction of neighborhood roads using paving blocks with a total length of 3,038 meters and drainage channels using U-Ditch and stone masonry with a total length of 3,994 meters. The total estimated cost required is IDR 3,671,111,028.53, consisting of 84.93% for road works and 15.07% for drainage works. The project implementation period is planned for approximately five months (155 days) based on the network planning analysis. The improvement of road and drainage infrastructure is a top priority to reduce slum conditions in Dutohe Village. It is recommended that the local government allocate budgets gradually and involve community participation to ensure sustainable settlement management and improve residents’ quality of life.